FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SEDIAAN BODY BUTTER EKSTRAK ETANOL UMBI BIT (Beta vulgaris L.) DENGAN METODE DPPH - Elisabeth Oriana Jawa La; Repining Tiyas Sawiji (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Beetroot (Beta vulgaris L.) is a plant that contains betasianin (purple pigment) and betasantin (yellow pigment) which makes the color of beets dark red to purplish. The fruit contains a small amount of flavonoid compounds (anthocyanins) which have antioxidant activity. This study aims to develop a body butter formulation of ethanol extract of beetroot (Beta vulgaris L.) as an antioxidant and to see the antioxidant activity with the DPPH immersion method. Extraction of beets used the maceration method using 70% ethanol as a solvent. The antioxidant activity test formula was measured using UV-Vis spectrophotometry with a wavelength of 520 nm. The results showed that formula I obtained an IC50 value of 240 µg/mL (AAI = 0.16), formula II obtained an IC50 value of 139.93 µg/mL (AAI = 0.28), and formula III obtained an IC50 value of 133.34 µg/mL (AAI = 0.29). The higher the antioxidant concentration of the fruit ethanol extract body butter preparation, the smaller the IC50 value, and the greater the AAI value obtained. Based on the results obtained, the antioxidants from the beetroot ethanol extract body butter were still able to fight free radicals at a weak level.